Tethered to the Cross: The Life and Preaching of C. H. Spurgeon. By Thomas Breimaier. Downers Grove, Ill.: IVP Academic, 2020. ix + 271 pp. $35.00 hardcover. - Chang, Geoffrey (Church history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009640721001281/resource/name/firstPage-S0009640721001281a.jpg